Arterial hypoperfusion as a negative predictive marker for primary hepatic malignancies treated with Y-90 glass microsphere transarterial radioembolization - Kalaghchi, Bita; Ince, Semra; Barnes, Justin; Kiser, Kendall; Chin, Re-I; Mikell, Justin; Badiyan, Shahed; Garcia, Jose; Zoberi, Jacqueline; Doyle, Maria Bernadette Majella; Tan, Benjamin; Kim, Seung; et al. (Frontiers in Oncology, 2024)
Radioembolization with yttrium-90 (Y-90) is utilized to treat primary liver malignancies. The efficacy of this intra-arterial therapy in arterially hypoperfused tumors is not known.We reviewed data of patients with primary liver tumors treated with Y-90 prescription doses of at least 150 Gy. Baseline patient characteristics, treatment history, imaging-based tumor response assessments, and clinical outcome metrics were recorded. Tumors were classified as arterially hyperperfused versus hypoperfused on post-TARE Y-90 SPECT/CTs or pre-TARE hepatic perfusion SPECT/CTs. Perfusion status was correlated with tumor response assessments and clinical outcomes. Cox proportional hazards models were utilized to compare survival and progression-free survival. Inverse probability weighting was utilized to account for clinical factors and adjusted multivariable proportional hazards analyses to examine the relationship of quantitative perfusion and cancer outcomes.Of 400 Y-90 treatments, 88 patients received a prescribed dose of at least 150 Gy and had pre-or post-treatment SPECT/CT images. 11 and 77 patients had arterially hypoperfused and hyperperfused lesions, respectively. On dedicated liver MRI or CT at 3 months after Y-90, the complete response rates were 5.6% and 16.5% in the hypoperfused and hyperperfused cohort, respectively (P = 0.60). When controlling for various clinical features, including tumor histology, patients with arterially hypoperfused tumors had significantly shorter progression-free survival (HR 1.87, 95% CI -1.03 -3.37, P = 0.039) and greater elsewhere liver (HR 3.36, 95% CI = 1.23 -9.20, P = 0.019) and distant failure (HR 7.64 (2.71 -21.54, P < 0.001). In inverse probability weighted analysis, patients with arterially hypoperfused tumors had worse overall survival (P = 0.032). In the quantitative analysis, lower levels of lesion perfusion were also associated with worse clinical outcomes, again controlling for tumor histology.Compared to arterially hyperperfused tumors, hypoperfused primary liver tumors treated with Y-90 may have worse clinical outcomes.